2016
DOI: 10.1016/j.envres.2016.07.034
|View full text |Cite|
|
Sign up to set email alerts
|

APOE ε4 allele modifies the association of lead exposure with age-related cognitive decline in older individuals

Abstract: Background Continuing chronic and sporadic high-level of lead exposure in some regions in the U.S. has directed public attention to the effects of lead on human health. Long-term lead exposure has been associated with faster cognitive decline in older individuals; however, genetic susceptibility to lead-related cognitive decline during aging has been poorly studied. Methods We determined the interaction of APOE-epsilon variants and environmental lead exposure in relation to age-related cognitive decline. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Our results also support the link of Pb with cognitive domains of processing speed, sustained attention, and working memory (DSST) and to a lesser degree for composite cognitive score. We note that published evidence suggests strong links between Pb and various measures of later-life cognitive performance, such as with cognitive decline (16,18,19,55), eye-hand coordination (56), executive functioning, and verbal memory and learning (56,57). In bringing these individual pathways together in mediation analysis, we demonstrated that 4% of racial disparities in DSST score was mediated through higher patella Pb among Black participants vs. White participants.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Our results also support the link of Pb with cognitive domains of processing speed, sustained attention, and working memory (DSST) and to a lesser degree for composite cognitive score. We note that published evidence suggests strong links between Pb and various measures of later-life cognitive performance, such as with cognitive decline (16,18,19,55), eye-hand coordination (56), executive functioning, and verbal memory and learning (56,57). In bringing these individual pathways together in mediation analysis, we demonstrated that 4% of racial disparities in DSST score was mediated through higher patella Pb among Black participants vs. White participants.…”
Section: Discussionmentioning
confidence: 58%
“…The etiologic window encompassing initiation of physiological processes and accumulation of damage leading to abnormal cognitive decline is thought to span years to decades (2,12). Epidemiological evidence consistently and robustly links environmental Pb to accelerated cognitive aging, poorer laterlife cognitive function, AD diagnosis and AD-related mortality (12,16,17,18,19). Due to historic and continuing trends of systemic environmental injustice and segregation in the U.S. driving poverty and deteriorating housing and water infrastructure, racial disparities of higher yet avoidable Pb exposure have been tracked since the 1970s and persist currently (11).…”
Section: Introductionmentioning
confidence: 99%
“…(2016) only found such an association in individuals with apolipoprotein E (APOE) ε4ε4 genotypes 37,39 . It should be emphasized that while cognitive impairment may sometimes be a precursor of AD, this is not invariably so 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no study to date has performed a multi-dimensional analysis of the associations between lifestyle behaviors and education in relation to obesity. This lack leaves studies of obesity far behind those of other health outcomes or of risk factors in exploring the interplay between or among various influencing factors [ 13 , 14 ], and may also be a barrier to developing theories and designing appropriate policies for reducing obesity.…”
Section: Introductionmentioning
confidence: 99%